Illusory Wage Differentials: Reply - Lazear, Edward P. (American Economic Review, 1984)
We are quick to add, however, that the difference in estimated OJT across the two groups is not large in 1966. In fact, H(1966)ID=1 H(1966)|D=O = $0.55 (with a standard error of $0.67) so that the difference is relatively small and the standard error is quite large. The conclusion is then that for this early period, the measured wage differential underestimates the true differential, but the extent of that understatement is questionable. [p. 559]